ОСОБЕННОСТИ ТЕОРЕТИЧЕСКИХ МОДИФИКАЦИЙ ТАЙНОЗНАНИЯ В СРЕДНЕВЕКОВОЙ КУЛЬТУРЕ - Гринева, Н. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Проанализированы основные особенности теоретических модификаций тайнознаниясредневековья, которые теперь точнее называть условно-теоретическими, т.к. главнымисточником познания мира в христианстве считается Божественное откровение, котороепостигается не с помощью научно-теоретических доказательств, а в акте веры. Определенагенетическая функциональная родственность христианства и тайнознания. Выявленопарадоксально-двойственное отношение официального христианства к тайнознанию.Прослежены трансформации социокультурных функций тайнознания.Гриньова Н.В. Особливості теоретичних модифікацій таємнознавства в середньовічнійкультурі. Проаналізовано основні особливості теоретичних модифікацій таємнознавствасередньовіччя, які точніше було б називати умовно-теоретичними, оскільки головним джереломпізнання світу в християнстві вважається Божественне откровення, яке осягається не задопомогою науково-теоретичного пізнання, а в анті віри. Визначено генетичну і функціональнуспорідненість християнства і таємнознавства. Виявлено парадоксально-двоїсте ставленняофіційного християнства до таємнознавства. Простежено трансформації соціокультурнихфункцій таємнознавства.Grinjova N.V. Peculianties of theoretical modifications of cryptoknowledge in medievalculture. The main peculianties of theoretical modifications of medieval cryptoknowledge are analysedwhich should be accrunately called relatively theoretical as the main sourse of global knowledge inChristianity is Gods revelation.This revelation is perceived using scientific and theoretical proofs as wellbelief. The genetic functioning likeness of Christianity and cryptoknowledge is determined. The paradoxtwo-faced attitude of the official Christianity to the cryptornowledge on the whole and the witchcraft, inparticular is revealed. The transformations of social and cultural functiouns of cryptoknowledge inmedieval culture.